Exercise therapy as a digital therapeutic for chronic disease management: consideration for clinical product development - Grannell, Andrew; Hallson, Hallur; Gunlaugsson, Birkir; Jonsson, Hedinn (Frontiers in Digital Health, 2023)
Digital exercise therapies (DET) have the potential to bridge existing care gaps for people living with chronic conditions. Acting as either a standalone, embedded within multi-modal lifestyle therapy, or adjunct to pharmacotherapy or surgery, evidence-based DETs can favorably impact the health of a rapidly growing population. Given the nascent nature of digital therapeutics, the regulatory landscape has yet to mature. As such, in the absence of clear guidelines clinical digital product developers are responsible for ensuring the DET adheres to fundamental principles such as patient risk management and clinical effectiveness. The purpose of this narrative review paper is to discuss key considerations for clinical digital product developers who are striving to build novel digital therapeutic (DTx) solutions and thus contribute towards standardization of product development. We herein draw upon DET as an example, highlighting the need for adherence to existing clinical guidelines, human-centered design and an intervention approach that leverages the Chronic Care Model. Specific topics and recommendations related to the development of innovative and scalable products are discussed which ultimately allow for differentiation from a basic wellness tool and integration to clinical workflows. By embodying a code of ethics, clinical digital product developers can adequately address patients' needs and optimize their own future digital health technology assessments including appropriate evidence of safety and efficacy.